AREA PERTEMPURAN BANGKO PADA MASA PERJUANGAN MEMPERTAHANKAN KEMERDEKAAN REPUBLIK INDONESIA 1945-1949 - Nopfrilian, Jepmi; Kaksim, Kaksim; Kharles, Kharles (Pendidikan Sejarah, 2014)
This thesis examines the Area of battle in Bangko in maintaining the independence of Indonesia. When the first Aggression of Netherlands, Bangko dont get meaningful attack from the Netherlands, but on the second Aggression Bangko attacked Netherlands. The results of this study showed that : after the Netherlands attacked the Jambi City on second aggression, Netherlands continue to assault Bangko, with the purpose to control rubber plantations and attacked military Government that moved from jambi to the Tanjung Dalam(Jangkat). Second after the Netherlands Entered terrain Bangko began thinking about the steps that will be taken by forming the youth keep security like API, PRI, BPKM and BKR, a battle in the region of Kewedanaan Bangko, Batang Asai, Sarolangun, and Lubuk Resam. This is evidenced from the many battles that occurred in the region such as : the battle at Mandiangin, Sarolangun, Dusun Tanjung, Kubang Ujo, Sungai Pinang, Rantau Panjang, and Merkeh.